Mountains as Earth’s Stakes in the Perspektive of the Qur’an: An Interdisciplinary Study of Qur’anic Exegesis and Geological Science - Mazaya Fuadaha; Faishal Abdullah (International Journal of Islamic Studies Issues, 2025)
This research examines the concept of mountains as Earth’s Stakes through an interdisciplinary lens, integrating Qur'anic perspectives with modern geological science. The study aims to bridge the gap between classical and modern exegesis (tafsir), specifically focusing on Tafsir Ibn Kathir and Quraish Shihab’s Tafsir Al-Misbah, and contemporary scientific understanding. The study employs an interdisciplinary approach, synthesizing qualitative textual analysis of religious scriptures with established scientific theories. It compares the linguistic and theological descriptions of mountains in the Qur'an (specifically Surah An-Naba: 6-7) with empirical geological data, including plate tectonics and the principle of isostasy. The results indicate that the Qur'anic term "autad" (stakes) aligns with modern geological findings which reveal that mountains have deep "roots" embedded in the Earth's crust. These structures contribute to the Earth's geodynamic stability, mitigate seismic impacts, and provide essential resources for life. Furthermore, the study finds that while classical interpretations focus on physical stability, modern interpretations expand this to include the spiritual significance of divine balance in creation. This research demonstrates a profound harmony between divine revelation and empirical science. By validating the stabilizing function of mountains through both theological and scientific frameworks (including perspectives from scholars like Keith L. Moore), it provides a foundation for developing faith-based scientific knowledge and encourages a holistic view of the relationship between religion and the natural world.